Pengenalan Kewirausahaan Dan Wirausaha Digital Pada Ma An-Nur Pagar Jati Kota Bengkulu - Irwandi, Abdurrahman; Soleh, Ahmad; Irwanto, Tito; Astuty, Kamelia (Jurnal Dehasen Untuk Negeri, 2025)
At MA AN-NUR Pagar Jati, Bengkulu City, students are a small group of people who will face the world of work to meet their financial needs. Currently, the industrial world is moving very fast, so students must be able to keep up with the times. This introduction to entrepreneurship and digital entrepreneurship aims to foster creative, innovative, independent, leadership attitudes, being good at managing money, and having a spirit of never giving up are some of the entrepreneurial attitudes that need to be instilled in students. Currently, it is very important to use social media in the sales system in order to increase promotions and increase sales throughout the world easily without spending a lot of money. This starts from an introduction to the target regarding the importance of knowing (digital marketing) for entrepreneurship where the world of digital marketing from year to year to the next will always be used and always in the future because in the current era it is a digital era. The introduction of entrepreneurship and digital entrepreneurship that is taught is expected to be able to reduce consumerist patterns in children by training them to create something of value and bringing the next generation to create jobs in the future